Inadequate N application of rice farmers in the Philippines: Problems, causes, solutions - Roehlano M. Briones (Philippine Institute for Development Studies (PIDS), 2016)
Inadequate application of nitrogen (N) fertilizer has been identified by the Food Staples Sufficiency Program as a major constraint in achieving rice self-sufficiency. The available literature on fertilizer application in the Philippines tends to find inadequate N application under the agronomic and economic criteria. Explanations for the gap may be grouped under the following sets of factors: external constraints, attitude toward risk, and internal constraints. Different explanations imply different policy solutions, hence, it is critical to correctly identify the most relevant explanations. A new estimation using FAO Fertibase data confirms the finding of inadequate N application by rice farmers in the Philippines. Additional study is proposed covering the following: (1) comparing actual to optimal N application using secondary data for Central Luzon (obtained from the International Rice Research Institute) and (2) identifying the reasons for inadequate N application using primary data collected from a survey of rice farmers in Nueva Ecija.
Keywords: 330; efficiency; fertilizer; yield gap; risk aversion; prospect theory; behavioral economics